Guaianolide sesquiterpenoids from Ainsliaea yunnanensis. (July 2017) - Fang, Xin; Xu, Xi-Ke; Wang, Guo-Wei; Zeng, Ren-Tao; Tian, Xin-Hui; Shi, Zhi-Ran; Zhuo, Zhi-Guo; Shen, Yun-Heng; Zhang, Wei-Dong
Abstract: Six previously undescribed C17 -guaianolides, a previously undescribed guaianolide alkaloid, and two previously undescribed guaianolides as well as 10 known guaianolides were obtained from an ethanol extract of Ainsliaea yunnanensis Franch. The chemical structures of all previously reported sesquiterpenoids were determined by extensive NMR spectroscopic analysis in combination with a modified Mosher's method. All isolates were in vitro screened for inhibitory effect against nitric oxide release in RAW 264.7 macrophages stimulated by LPS. Zaluzanin C remarkably inhibited the production of nitric oxide with an IC50 value of 6.54 μM. Graphical abstract: Highlights: Nine previously unreported sesequiterpenoids were isolated. Yunnanolides A-F are rare C17 -guaianolides. Yunnanolide G is an unusual γ -butyrolactam substituted guaianolide. Zaluzanin C remarkably inhibited NO release in LPS-induced RAW264.7 macrophages.